GROUP THERAPY SUPPORT FOR WOMEN WHO SURVIVE INTRAFAMILIAL VIOLENCE - Mora-Escalante, Elena (2005)
The specific violence against women is a reflection of the inequality andinferiority constructed against them  in a society of power against one another. One of the terrible effects of the continuous violence and abuse is that these women learn to live without hope.  Because of the above, it was very important to develop of support groupsanswering the needs of these survivors of intra-familial violence. Thedevelopment of this therapy used a phenomenological perspective and Sensitive Gender. The phenomenological perspective was based on a humanistic. In addition, there was the qualitative methodology. The group therapy was done with the afore-mentioned views and oriented to explore the central axis of the areas that were affected by intra-familial violence, to express  feelings, to produce behavior and cognitive changes.   The methods that were used in the support group were that everyone pays attention to the behaviors, the ideas, and the expressions of each woman a thing that stimulated the oriented group to encourage the women in therapy to be the ones who recognized the tools to confront the violence with which they lived.